1982
DOI: 10.1111/j.1751-1097.1982.tb04400.x
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity, Dna Damage and Inhibition of Dna Repair Synthesis in Human Melanoma Cells by Concentrated Sunlight

Abstract: A 1 m diameter water lens was used to focus solar radiation, giving an 8‐fold concentration of the total spectrum and a cytocidal flux similar to that of laboratory UV sources. Survival curves for human melanoma cells were similar for sunlight and 254 nm UV, in that Dq, was usually larger than Do. An xeroderma pigmentosum lymphoblastoid line was equally sensitive to both agents and human cell lines sensitive to ionizing radiation (lymphoblastoid lines), crosslinking agents or monofunctional alkylating agents (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

1985
1985
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 24 publications
2
12
0
Order By: Relevance
“…Parsons and Musk (1982), comparing normal and XP-A cells, found that at 254 nm the XP cells were 8.5 times as sensitive as normal cells, while when exposed to sunlight they were only 6.0 times as sensitive. Keyse et al (1983) showed that XP12BE cells (a different complementation group A cell strain than those used by Parsons and Musk, 1982) became progressively less sensitive, compared with normal cells, at wavelengths above 313 nm, until they were similar in response at 365 nm. But, Patton et al (1984) saw no differences in relative responses to 254 nm and sunlamp irradiation among a variety of XP (including XP12BE) and normal cell strains.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Parsons and Musk (1982), comparing normal and XP-A cells, found that at 254 nm the XP cells were 8.5 times as sensitive as normal cells, while when exposed to sunlight they were only 6.0 times as sensitive. Keyse et al (1983) showed that XP12BE cells (a different complementation group A cell strain than those used by Parsons and Musk, 1982) became progressively less sensitive, compared with normal cells, at wavelengths above 313 nm, until they were similar in response at 365 nm. But, Patton et al (1984) saw no differences in relative responses to 254 nm and sunlamp irradiation among a variety of XP (including XP12BE) and normal cell strains.…”
Section: Discussionmentioning
confidence: 98%
“…those of wavelength longer than 286 nm, recent studies have used both monochromatic (Coohill et al, 1983;Han et al, 1984;Keyse et al, 1983;Peak et al, 1985a;Peak er al., 1985b;Roza et al, 1985;Rosenstein and Ducore, 1983;Tyrrell and Amaudruz, 1984;Zelle et al, 1980;Zolzer and Kiefer. 1984;Tyrrell and Amaudruz, 1984;Zelle et af., 1980;Zolzer and Kiefer, 1984) and polychromatic sources (Erickson et al, 1980;Holmberg al., 1985;Jacobson and Krell, 1982;Patton et al, 1984;Suzuki et al, 1981;Zamansky, 1986) and even "natural" (incident on the Earth's surface) sunlight (Kantor and Ritter, 1983;Kantor and Ritter, 1984;Kantor, 1985;Parsons and Musk, 1982;Parsons and Hayward, 1985). Each of these sources has its limitations.…”
Section: Introductionmentioning
confidence: 99%
“…A number of large animal models of melanoma have been described, including Sinclair swine (http://www.cvm.tamu.edu) and Camargue horses (9), neither of which have melanomas with a sunlight etiology. Angora goats, however, develop a lentiginous melanoma similar to a form of melanoma observed in the elderly (10) in response to chronic sunlight exposure at a rate of about 2% (11). More accessible to experimentation, however, are the non‐mammalian Xiphophorus fish model and the marsupial opossum, Monodelphis domestica , both of which have been used to study the photobiology and genetics of melanoma.…”
Section: Animal Models For Melanomamentioning
confidence: 99%
“…For cells exposed to UV wavelengths in this range, the ratio of various nondimer DNA damages, including DNA strand breaks [Rosenstein and Ducore, 19831, DNA-protein cross-links [Han et al, 1984;Peak et al, 19851, and thymine glycols [Hariharan and Cerutti, 19771, to dimers is 10-1,000-fold higher than in 254-nm-irradiated cells. In addition, the results of a series of experiments performed in recent years in a variety of laboratories have demonstrated that these nondimer damages play a significant role in cells exposed to solar UV wavelengths [Parsons and Goss, 1980;Zelle et al, 1980;Ritter and Williams, 1981;Smith and Paterson, 1981;Suzuki et al, 1981;Parsons and Musk, 1982;Keyse et al, 1983;Miguel and Tyrrell, 1983;Rosenstein, 1984a,b;Turner and Eisenstark, 1984;Tyrrell, 1984a,b;Wells and Han, 19841. Hence, the purpose of this research was to investigate the excision repair of these nondimer DNA lesions in comparison with the repair of dimers employing the metabolic inhibitors HU and ara C.…”
Section: Introductionmentioning
confidence: 99%